PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU PROSOSIAL PESERTA DIDIK KELAS TINGGI DI YPS MI MANGGARUPI KABUPATEN GOWA - Widiastuti, Widiastuti; Yahdi, Muhammad; Rahman, Ulfiani; Suarti, Suarti (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
This study discusses the effect of parenting on the prosocial behavior of high-class students at YPS MI Manggarupi, Gowa Regency. This study aims to determine the parenting patterns of high-class students at YPS MI Manggarupi, Gowa Regency, to determine the prosocial behavior of students in high-class students at YPS MI Manggarupi, Gowa Regency and to determine the effect of parenting on students’ prosocial behavior. high class at YPS MI Manggarupi, Gowa Regency. This research is a quantitative research, using the ’ex post facto’ method. The research subjects were high-class students at YPS MI Manggarupi, Gowa Regency with a total of 77 of 154 students who were taken using the Simple Random Sampling technique. Data collection techniques were carried out through closed questionnaires and documentation. Data analysis used descriptive quantitative analysis and inferential analysis. Based on the results of the analysis, it was found that the parenting pattern of high-class students YPS MI Manggarupi Sungguminasa, Gowa Regency was in the very good category, namely 62.34%, the prosocial behavior of high-class students YPS MI Manggarupi Sungguminasa, Gowa Regency was in the very good category, namely 70, 13%, and there is a significant effect of parenting on prosocial behavior. This can be proven by the t-test which gets tcount of 15.942 where ttable is 0.2242 and b1 coefficient is 0.012 with a probability of 0.020 <0.05. Meanwhile, the effective contribution of parenting style to prosocial behavior is 77.2%.